Surgical treatment of benign endobronchial tumours - Halttunen, P (1982)
Four cases of benign endobronchial tumour are reported which were successfully treated by bronchial resection. In two cases (of fibroma and leiomyoma respectively) a cylinder of bronchus alone was resected; in one case (lipoma) a healthy right upper lobe was preserved by a bronchoplastic procedure and in the other (chondroma) the tumour was removed with the right lower lobe, which was irreversibly damaged. It is important to recognise that such tumours are unsuitable for treatment by endoscopic means alone.